Inovasi Pembelajaran Fluida Dinamis dengan Discovery Learning dan Alat Peraga: Dampak pada Kreativitas dan Pemahaman Siswa - Darojat, Dede Jakiyah; Zakirman, Zakirman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to improve students' conceptual understanding and creativity in dynamic fluid materials through the application of the Discovery Learning model assisted by simple props. This type of research is a classroom action research involving grade XI science students at the Adzkiya Integrated MA as a sample. Data collection instruments include creativity assessment sheets and multiple-choice tests to measure concept understanding. The research was carried out in two cycles from April to May 2024. The results of the research in the first cycle identified several obstacles, both in terms of teachers, students, and technical aspects. Shortcomings in the first cycle include non-optimal division of groups that are not conducive, lack of enthusiasm and motivation of students to conduct investigations and problem-solving, and exceed the specified time allocation. In the second cycle, there was a significant increase. Students show higher enthusiasm and motivation to learn, as well as good liveliness and cooperation in group discussions, so that the learning process runs more effectively and in accordance with the set time allocation. These results show that the application of the Discovery Learning model assisted by simple props can improve students' conceptual understanding and creativity in dynamic fluid materials. This study suggests optimizing group division and time management for maximum results in future learning implementation.